A new model for predicting the viscosity of heavy oil. (2nd May 2016) - Liu, Yonghui; Shi, Shuqiang; Wang, Yongqing; Xie, Jiang; Xie, Gang
ABSTRACT: Models of heavy oil viscosity are considered as a function of temperature and API gravity in literature at home and abroad, and the API gravity is measured under the condition of 20°C, but without considering the effect of temperature on the API and colloid asphalt content in heavy oil. A total of 197 data points from 41 samples of Huabei oilfield are tested from previous studiesand five other heavy oil viscosity models, and the calculation value is much less than the measured value. The new prediction model of heavy oil viscosity is established by Simplex Method and the General Global Optimization Method. The new model takes into account the temperature, API, colloid asphalt, and the influence of temperature on API. Using the new model to predict the viscosity of heavy oil samples of Huabei oilfield, the average relative error of 3.36%, mean absolute error of 7.61%. The new prediction model is precise than other eight models, calculated values and measured values coincide when degree is higher.